Resting the mind - A novel topic with scarce insights. Considering potential mental recovery strategies for short rest periods in sports - Loch, F.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M. (Performance Enhancement & Health, 2019)
Both meticulously structured trainig routine as well as specific characteristics of various sports (e.g., swimming, shooting, modern pentathlon) with multiple competition bouts in a single day appear to be mentally demanding and may result in a state of mental fatigue. Due to these multidimensional demands, adequate training and competition recovery is essential. Consequently, the idea of mental recovery embraces the spotlight of research. On training and competition days, short rest periods implemented as a vital part, can be used for mental recovery and can help in assisting athletes to return to baseline levels of mental abilites (e.g., concentration, attention). Sport-specific investigations of potential mental recovery strategies and their effects on an athlete`s mental percepetion are lacking. As a starting point, this scoping review specifiy mental recovery and summarise current knowledge of mental recovery strategies which athletes can use to buffer mental demands (countermeasure of mental fatigue outcomes) throughout a training or competition day. The implementation of mental recovery strategies might open additional opportunities to improve mental as well as sport-specific performance by minimising the mental load and by optimising recovery in a systematic way. Based on practical notes, further studies focusing on intervention effects of mental recovery strategies in applied sport are required.